Gear meshing analysis of planetary gear sets with a floating sun gear. (February 2015) - Tsai, Shyi-Jeng; Huang, Guan-Lin; Ye, Siang-Yu
Abstract: The goal of this study is to propose an analytical approach for analysis of gear meshing in a planetary gear set with a floating sun gear. With focus on the basic geometrical relation, we derive a set of equations based on the exact involute gear geometry for calculation of the tooth clearances among engaged unmodified or modified flanks of gears having relevant errors. Two constraint conditions for the floating sun gear are established for determination of the movable area. Numerical examples are presented to explore the influences of the planet gear number, the backlashes, and the assembly/manufacturing errors on the tooth clearance, the moveable area and assemblability of the sun gear. Highlights: An analytical approach based on the exact involute gear geometry is proposed. It is suitable and effective for analysis of gear meshing of the planetary gear. The constraint types of the floating sun gear are studied. The movable area and the assemblability of the sun gear are analyzed. The relation between tolerances for backlash and allowable errors is studied.